Soluções ondas viajantes da equação Korteweg-de Vries-Burgers - Silva, Eliza Souza da (Universidade Federal de São Carlos, 2006)
The aim in this work is to estudy the existence and certain qualitative properties of travellingwave to the Korteweg-de Vries-Burgers (KdVB) equation. The asymptotic behaviour of these waves is analysed when ε ↓ 0, δ ↓ 0 or when both ε,δ ↓ 0, subject to the determined conditions.
Keywords: Equações diferenciais parciais; Burgers, equação de; Equação de Korteweg-de Vries; Ondas não lineares; CIENCIAS EXATAS E DA TERRA::MATEMATICA